Evaluation of the relationship between coronary slow flow phenomenon and serum magnesium levels (Annals of Medical Research, 2021)
Aim: Splint use is often recommended following wrist injection patients diagnosed with carpal tunnel syndrome (CTS), but there is not any data in the literature pertaining to the impact of splint treatment, used before injection, on the results of local injection treatment. The aim of this study to evaluate whether or not splint use starting before the injection would impact the local injection treatment outcomes.Materials and methods: Fifty seven patients (57 hands) with CTS and underwent ultrasound-guided injection were included in the study, and patients were divided into two groups in terms of splint use. Median nerve cross-sectional area (MNCSA), pain/numbness by visual analogue scale (VAS), symptoms and functionality by Boston Carpal Tunnel Questionnaire (BCTQ) were investigated before injection and 15 days after injection.Results: There was significant change over time in MNCSA, VAS, and BTCQ scores in groups. The patients not using splint group had significantly higher percentage change in VAS nighttime score.Conclusion: Our findings has shown that using neutral wrist splint, starting before and continuing after injection treatment, did not increase the injection treatment efficacy and may actually have negative effect on improvement in VAS nighttime scores.
Keywords: Median nerve; sonography; splinting; steroid injection